Genomics : a revolution in health and disease discovery - Stewart, Whitney, 1959-; Andersson, Hans Christoph, 1956- (Twenty-First Century Books, 2021)
Examines the research breakthroughs in genetic studies since the completion of the Human Genome Project that have changed how researchers look at inheritance, health, medicine, ancestry, and epigenetics.